Potentialities and Limits of Some Non-thermal Technologies to Improve Sustainability of Food Processing - Picart-Palmade, Laetitia; Cunault, Charles; Chevalier-Lucia, Dominique; Belleville, Marie-Pierre; Marchesseau, Sylvie (Frontiers in Nutrition, 2019)
In the whole food production chain, from the farm to the fork, food manufacturing steps have a large environmental impact. Despite significant efforts made to optimize heat recovery or water consumption, conventional food processing remains poorly efficient in terms of energy requirements and waste management. Therefore, in the few last decades, much research has focused on the development of alternative nonthermal technologies. Some of them, such as membrane separation processes, hydrostatic or dynamic high pressure, dense phase or high-pressure carbon dioxide, pulsed electric fields have been extensively studied for cold pasteurization, concentration, extraction, or food functionalization. However, it is still difficult to evaluate the actual advantages or limits of these innovative processing technologies to replace conventional processes. Thus, the overall aim of this paper is to present an overview of the most relevant studies dealing with the potentialities and limits of these nonthermal technologies to improve sustainability of food processing. After a brief presentation of the physical principles of these technologies, the paper illustrates how these technologies could play a decisive role for sustainable food preservation or valorization of raw materials and by-products.